The Integration of Knowledge, Economical, and Technological Concepts in the Pre-Vocational Education and Sciences Education Curriculum as Perceived by the Teachers at Irbid Directorate Schools - Al-Alawneh, Muhammad; Mustafa, Jehad (Jordan Journal of Educational Sciences, 2014)
The Integration between pre-vocational education and sciences education curricula is fundamental for understanding the nature of sciences and their applications. Therefore, this study was conducted to assess the degree of integrating knowledge, economical, and technological concepts in the pre-vocational education and sciences education curriculum as perceived by the teachers of both subjects, and whether these perspectives differ due to the study’s independent variables. A descriptive cross sectional study using a survey to collect the data from 189 teachers from Irbid Educational Directorate was done in the second semester of 2013. The instrument was developed by the researchers after an extensive review of the literature and based on the related previous studies. The results showed that teachers in sciences education and pre-vocational education assessed the integrating of these three concepts on moderate scale, and there was a significant difference between the teachers’ perspectives on the technological domain based on the teachers’ major. The study concludes with recommendations and implications for future research